2018
DOI: 10.1111/edt.12401
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of Thai propolis on human osteoclastogenesis

Abstract: Thai propolis can inhibit human osteoclast formation and function, which may be beneficial for prevention of root resorption following replantation of avulsed teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Some substances tested to treat the root surface before delayed tooth replantation have efficacy as osteoporotic therapeutic agents that inhibit osteoclast activity and modulate immune inflammatory reactions. 6,7,8 These substances include Emdogain, alendronate, odanacatib 6 and propolis. 7,8 In recent years, compounds of natural origin, obtained from plants such as curcumin and piperine, have been tested to formulate anti-inflammatory and antiosteoclastogenic drugs having the potential to treat and prevent replacement resorption of replanted teeth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some substances tested to treat the root surface before delayed tooth replantation have efficacy as osteoporotic therapeutic agents that inhibit osteoclast activity and modulate immune inflammatory reactions. 6,7,8 These substances include Emdogain, alendronate, odanacatib 6 and propolis. 7,8 In recent years, compounds of natural origin, obtained from plants such as curcumin and piperine, have been tested to formulate anti-inflammatory and antiosteoclastogenic drugs having the potential to treat and prevent replacement resorption of replanted teeth.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,8 These substances include Emdogain, alendronate, odanacatib 6 and propolis. 7,8 In recent years, compounds of natural origin, obtained from plants such as curcumin and piperine, have been tested to formulate anti-inflammatory and antiosteoclastogenic drugs having the potential to treat and prevent replacement resorption of replanted teeth. 9 In this respect, a recent study tested the effect of a plant lectin on stimulated gingival fibroblasts, with promising results 10 for future use as a possible therapy for delayed replanted teeth.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that disruption of periostin‐mediated homeostatic relationship within fibrous connective tissues of the PDL might lead to a deteriorated biomechanical properties of the PDL, providing that periostin is a key element required for collagen I fibrillogenesis in variety of connective tissues 28 . Wimolsantirungsri et al showed that Thai propolis extract can inhibit human osteoclast formation and function, 29 which may be beneficial for prevention of root resorption following replantation of avulsed teeth. Collectively, these findings might suggest that Thai propolis extract when used in moderation as a storage medium enables PDL cells to preserve their characteristics of periostin mRNA expression for up to 12 hours extra‐oral dry time.…”
Section: Discussionmentioning
confidence: 99%
“…For in vitro osteoclastogenesis studies, mouse marrow cells, human peripheral blood mononuclear cells, and RAW264.7 cell line were the cell models used. Mouse marrow and RAW264.7 cell were stimulated with receptor activator of NF-kB (RANK) ligand (RANKL) and cultured with 1-10 µL of propolis [39], while human peripheral blood mononuclear cells were stimu-lated with macrophage colony-stimulating factor (M-CSF) and RANKL and cultured with 0.025-10 mg/mL of propolis [40]. For osteoblastogenesis studies, the cell models used were MC3T3-E1 and MG-63 cell lines.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Overall, 2 studies showed that propolis suppressed osteoclastogenesis [39,40], while 2 studies showed that propolis promoted osteoblastogenesis [41,42]. In the animal experiments, propolis inhibited bone loss due to periodontitis in 2 studies [48,49], bone loss due to periodontitis/STZ-induced diabetes in 1 study [56], bone loss due to OTM in 3 studies [50][51][52] and bone loss due to dental implantitis in 1 study [41].…”
Section: Study Characteristicsmentioning
confidence: 99%